Integrating Buddhist Ethics into Boarding School Education : Character Development at Pasastrian Kusalamitra, Gunung Kidul, Indonesia - Jovini, Jovini; Sutikyanto, Sutikyanto; Andanti, Maria Fransisca (LPPM Universitas Pendidikan Mandalika, 2024)
This study aims to explore Buddhist character values focused on the educational processes at Pasastrian Kusalamitra Gunung Kidul and how these values are implemented within the boarding school context to develop student character. The study method used was descriptive with a qualitative approach, including interviews, focus group discussion, direct observation, participant observation, and document review. The subjects of this study included key individuals directly involved in educational programs, comprising the principal and vice principal of PKBM Homeschooling Kusalamitra, twelfth-grade teachers and students, selected for their significant roles in and deep engagement with the schoolâ€™s activities. Data collected were analyzed using NVivo 14, employing thematic analysis to develop codes and themes, guided by description-focused coding, which involves extracting relevant statements, describing them, and tagging them for systematic categorization. Findings revealed that these Buddhist virtues significantly enhanced students' ethical orientations and personal growth, thereby boosting their academic and social skills. By deeply embedding these values within its educational framework, Pasastrian Kusalamitra Â not only promoted holistic development but also equipped students with the resilience and empathy needed for modern societal interactions. Highlighting the transformative potential of religious ethics in education, the study suggests robust pathways for developing moral character in diverse learning environments.